THE INFLUENCE OF M-COMMERCE SERVICE AND SYSTEM QUALITY DIMENSIONS ON OVERALL PERCEIVED SERVICE QUALITY - Salameh, Anas Abdelsatar; Hassan, Shahizan Bin; Alekam, Jamal Mohammad (International Journal of Research -GRANTHAALAYAH, 2015)
Information Technology (IT) has an increasing importance and development in business life. Nowadays, businesses have been seeking to reach their customers through m-services especially m-commerce. The concern is to what extent this m-commerce system can satisfy the consumers’ needs and contributes to the overall online purchasing development. This study aims to examine the effect of m-commerce service quality dimensions (website design, responsiveness, and trust), and system quality dimension (accessibility) on overall perceived service quality in m-commerce by customers. The data were collected from the Arab Open University in Jordan through a self-administered questionnaire, in order to test the hypotheses of the proposed model. 618 of questionnaires were used for analysis data, out of 870 distributed. The result of this study revealed that there are a significant effect of responsiveness and accessibility on overall perceived service quality. This study has some important implications for business practice and research.